Equal Distribution of Needs for Health Workers in Southeast Sulawesi Province - Suatia, Wa Ode; Sunarsih, Sunarsih; Munir, Sanihu (Magister Kesehatan Universitas Mandala Waluya, 2024)
Introduction: The uneven distribution of health workers in Southeast Sulawesi Province can cause gaps in access and quality of health services. This study aims to analyze the distribution of health worker needs in the island and mainland areas of Southeast Sulawesi Province. Method: This type of research uses a Qualitative method with a descriptive approach. The respondents in this study were the Head of the Health Service and the Head of the Health Center as many as 20 people. Data analysis used Content Analysis. Result: The equal distribution of health workers needs in the island and mainland areas of Southeast Sulawesi Province still faces several problems in input factors. One of the main problems in the equal distribution of health workers is the uneven number of health workers in various regions, especially in the island and mainland areas. Some regions may experience a shortage of health workers, while other regions have excess or unbalanced concentration. This shortage of health workers can cause a heavy workload for existing health workers, reduce the quality of health services, and increase the risk of fatigue in health workers. Conclusion: It is necessary to address the uneven distribution of health workers with a strategic placement policy for health workers in island and mainland areas. The government must strengthen health infrastructure in remote and isolated areas.